Alkali free hydrolysis of sodium borohydride for hydrogen generation under pressure - M. J. F. Ferreira (2010)
The present study is related with the production of hydrogen gas (H 2), at elevated pressures and with high gravimetric storage density, to supply a PEM fuel cell on-demand. To achieve this goal, solid sodium borohydride (NaBH4) was mixed with a proper amount of a powder reused nickel-ruthenium based catalyst (Ni-Ru based/NaBH4: 0.2 and 0.4 g/g; ≈150 times reused) inside the bottom of a batch reactor. Then, a stoichiometric amount of pure liquid water (H2O/NaBH4: 2-8 mol/mol) was added and the catalyzed NaBH4 hydrolysis evolved, in the absence of an alkali inhibitor. In this way, this research work is designated alkali free hydrolysis of NaBH4 for H2 generation. This type of hydrolysis is excellent from an environmental point of view because it does not involve strongly caustic solutions. Experiments were performed in three batch reactors with internal volumes 646, 369 and 229 cm 3, and having different bottom geometries (flat and conical shapes). The H2 generated was a function of the added water and completion was achieved with H2O/NaBH4 = 8 mol/mol. The results show that hydrogen yields and rates increase remarkably increasing both system temperature and pressure. Reactor bottom shape influences deeply H2 generation: the conical bottom shape greatly enhances the rate and practically eliminates the reaction induction time. Our system of compressed hydrogen generation up to 1.26 MPa shows 6.3 wt% and 70 kg m-3, respectively, for gravimetric and volumetric hydrogen storage capacities (materials-only basis) and therefore is a viable hydrogen storage candidate for portable applications.